Avaliação da temperatura da câmara pulpar durante a cimentação de facetas pela técnica de resina composta termicamente modificada: um estudo “in-vitro” - Hans Hatner Araujo Oliveira (2022)
With the growing search for indirect esthetic restorations, the use of compatible materials and cementing techniques becomes essential for restorative success. Self-activated resin cements should not be used, due to the presence of tertiary amines in their composition. In these situations, the cementing agent of choice should be a light-cured resin material. The preheated composite (RTM in portuguese) technique makes it possible to use restorative composite resin as a cementing material, by applying heat in a controlled manner, improving its fluidity and other physical properties, but it can cause an increase in intrapulpal temperature. This study aimed to evaluate the increase in temperature in the pulp chamber of bovine teeth, with preparations for indirect restorations, cemented using the RTM technique. For this purpose, 80 bovine central incisors were selected and raffled via spreadsheet in the Excel program and grouped into 8 groups (n=10). Four groups were prepared for indirect veneers with different depths, namely: 2.0mm (G1), 1.5mm (G2), 1.0mm (G3), and 0.5mm (G4) and composite resin veneers were cemented using the RTM technique; the four remaining groups were prepared with the same depths 2.0mm (G5), 1.5mm (G6), 1.0mm (G7), and 0.5mm (G8) and veneers were cemented using photoactivated resin cement. A device developed to regulate pulp cavity temperature of ≅34ºC (±1.5ºC) and intrapulpal microcirculation of bovine incisors was used. A second device allowed the introduction of a temperature sensor into the intrapulpal chamber. Each tooth was individually coupled to the first device, and had the sensor of the second device inserted in its chamber and insertion of a temperature sensor in its pulp chamber. Intrapulpal temperature during cementation processes was measured, and data were analyzed via SPSS software. The groups cemented with RTM showed a higher average temperature variation in the pulp chamber, when compared to the groups in which veneers were cemented with photoactivated cement; groups with greater depth of preparation showed a greater mean variation (increase) in temperature in the pulp chamber. This study concluded that the factor that most contributed to the temperature increase in the pulp chamber in the RTM technique was the heat generated by heating the resin itself. The greater the depth of preparation, resulting in a smaller remaining dentin thickness, the greater the temperature variation in the pulp chamber.